Hydrogenation catalyst and preparation method thereof, and hydrogenation method of organic hydrogen storage material

By performing acid treatment and precipitation reaction on porous carbon materials, a catalyst with high hydrogenation efficiency and long service life was prepared, which solved the problems of poor stability and short service life of existing hydrogenation catalysts, and achieved efficient and safe hydrogenation effect of liquid hydrogen storage.

CN119657156APending Publication Date: 2025-03-21BEIJING HYWIN HYDROGEN ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411862228.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing liquid hydrogen storage hydrogenation catalysts have problems such as poor stability, short service life and low hydrogenation efficiency, which limits the large-scale application of organic liquid hydrogen storage technology.

Method used

By mixing the active metal component, the dispersing component, the additive metal precursor, the Al salt and the solvent, a salt solution is formed, and acid treatment and precipitation reaction are carried out on the porous carbon material, followed by calcination under an inert atmosphere, a catalyst with high hydrogenation efficiency and long service life is prepared.

Benefits of technology

The prepared hydrogenation catalyst exhibits high activity and stability during the hydrogenation process of liquid hydrogen storage, and can achieve safe hydrogen storage at a higher liquid space speed, reduce hydrogen storage energy consumption, reduce production costs, and improve the safety and stability of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657156A_ABST
    Figure CN119657156A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of catalysts, and discloses a hydrogenation catalyst and a preparation method thereof, and a hydrogenation method of an organic hydrogen storage material, the method comprises: (1) mixing an active metal component precursor, a dispersion component precursor, an auxiliary agent metal precursor, an Al salt and a solvent to obtain a salt solution; wherein the active metal component is selected from Ni and / or Co, the dispersion component is selected from Zn and / or Mg, and the auxiliary metal is selected from at least one of rare earth metal, VIIB group metal, IVB group metal and VIB group metal; (2) contacting the porous carbon with acid under a stirring condition to obtain acid-treated porous carbon; (3) mixing the acid-treated porous carbon, a salt solution, a surfactant and alkali, and carrying out precipitation reaction; and (4) roasting the product obtained in the step (3) in an inert atmosphere. The hydrogenation catalyst prepared by the method shows extremely high activity in the hydrogenation process of a hydrogen storage medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a hydrogenation catalyst and a preparation method thereof, and a hydrogenation method of an organic hydrogen storage material. Background Art

[0002] With the increasing attention paid to environmental protection around the world, achieving the "dual carbon" goal has become a development consensus among countries. In this context, the transformation of the energy structure has become a top priority, and the development and utilization of clean energy is the key to achieving this goal. Hydrogen energy, as a truly clean and environmentally friendly energy, is widely regarded as an important part of the future energy structure due to its abundant sources, clean and low carbon, high calorific value and high conversion rate. However, the wide explosion limit range and extremely low density of hydrogen pose great challenges to the storage and transportation of hydrogen energy.

[0003] In order to solve the problem of hydrogen storage and transportation, researchers have developed a variety of hydrogen storage technologies, including high-pressure gaseous hydrogen storage, low-temperature liquefied hydrogen storage, solid material hydrogen storage, and organic liquid hydrogen storage (LOHC). Among them, organic liquid hydrogen storage technology has occupied a place in the hydrogen storage and transportation market with its advantages of high density, high hydrogen storage efficiency, and high safety. The hydrogenation reaction of liquid hydrogen storage is an important process that can convert unsaturated organic compounds into saturated organic compounds. This process usually requires the use of catalysts to improve the efficiency and selectivity of the reaction. Among them, precious metal catalysts represented by Ru are currently the most commonly used hydrogenation catalysts. However, due to the scarcity and high price of precious metal resources, their large-scale industrial applications are limited. In order to solve this problem, researchers have conducted a lot of exploration and application on non-precious metals (such as Ni and Co), and have achieved certain research results. For example, CN112675865A discloses a method of using Al 2 O 3 -SiO 2 -La 2 O 3 The nickel-based catalyst with a composite oxide as a carrier has an arbitrary molar ratio of Al-Si-La in the catalyst. The coprecipitation method can increase the Ni loading to more than 30wt% on the one hand, and reduce the agglomeration of Ni on the other hand, thereby increasing the dispersion of Ni.

[0004] However, there are still some problems with today's liquid hydrogen storage hydrogenation catalysts. For example, during the hydrogenation process, traditional oxide carriers have a low specific surface area and poor dispersion of active metals, resulting in low metal utilization; and although carriers such as activated carbon have a large specific surface area, the interaction between the carrier and the metal is too weak. Since the hydrogenation process of organic liquid hydrogen storage is a liquid-solid phase reaction, long-term operation leads to serious loss of active metals. These problems limit the large-scale application of organic liquid hydrogen storage technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor stability, short service life and low hydrogenation efficiency of organic hydrogen storage material hydrogenation catalysts in the prior art, and to provide a hydrogenation catalyst and a preparation method thereof, and a hydrogenation method of an organic hydrogen storage material. The hydrogenation catalyst prepared by the preparation method has the characteristics of high hydrogenation efficiency and long service life.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a hydrogenation catalyst, the preparation method comprising: (1) mixing an active metal component precursor, a dispersed component precursor, an auxiliary metal precursor, an Al salt and a solvent to obtain a salt solution; Wherein, the active metal component is selected from Ni and / or Co, the dispersed component is selected from Zn and / or Mg, and the auxiliary metal is selected from at least one of rare earth metals, Group VIIB metals, Group IVB metals and Group VIB metals; (2) contacting the porous carbon with an acid under stirring conditions to obtain acid-treated porous carbon; (3) mixing the acid-treated porous carbon, salt solution, surfactant and alkali to carry out a precipitation reaction; (4) calcining the product obtained in step (3) under an inert atmosphere.

[0007] The second aspect of the present invention provides a hydrogenation catalyst prepared by the above preparation method.

[0008] A third aspect of the present invention provides a method for hydrogenating an organic hydrogen storage material, comprising: contacting an organic hydrogen storage material, hydrogen and a catalyst under hydrogenation reaction conditions; Wherein, the catalyst is the hydrogenation catalyst described in the second aspect.

[0009] Preferably, the organic hydrogen storage material is selected from aromatic hydrocarbon hydrogen storage materials and / or N-containing heterocyclic hydrogen storage materials. The aromatic hydrocarbon hydrogen storage material is preferably toluene and / or dibenzylcarbazole, and the N-containing heterocyclic hydrogen storage material is preferably at least one of carbazole, N-ethylcarbazole, N-methylcarbazole, and N-propylcarbazole.

[0010] The hydrogenation catalyst prepared by the preparation method of the hydrogenation catalyst provided by the present invention exhibits extremely high activity in the hydrogenation process of the hydrogen storage medium, can realize safe hydrogen storage at a higher liquid space velocity, can not only reduce the hydrogen storage energy consumption and production cost, but also help to improve the safety and stability of the production process. The method has the advantages of simple operation, cost reduction, easy promotion and environmental friendliness, and the preparation method has broader prospects and potential in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The graphs are the curves of the hydrogen storage capacity of the hydrogenation catalysts prepared in Example 1 and Comparative Example 1 over time. DETAILED DESCRIPTION

[0012] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0013] A first aspect of the present invention provides a method for preparing a hydrogenation catalyst, the preparation method comprising: (1) mixing an active metal component precursor, a dispersed component precursor, an auxiliary metal precursor, an Al salt and a solvent to obtain a salt solution; Wherein, the active metal component is selected from Ni and / or Co, the dispersed component is selected from Zn and / or Mg, and the auxiliary metal is selected from at least one of rare earth metals, Group VIIB metals, Group IVB metals and Group VIB metals; (2) contacting the porous carbon with an acid under stirring conditions to obtain acid-treated porous carbon; (3) mixing the acid-treated porous carbon, salt solution, surfactant and alkali to carry out a precipitation reaction; (4) calcining the product obtained in step (3) under an inert atmosphere.

[0014] The preparation method provided by the present invention, through the precipitation reaction in step (3), in the presence of a surfactant, in situ grows a hydrotalcite structure precursor on the porous carbon material after acid treatment, and then obtains a catalyst through calcination. The obtained catalyst has strong structural stability, can achieve efficient and stable hydrogenation of liquid hydrogen storage, and has a long service life. The reason may be that through the above-mentioned preparation method, the hydrotalcite structure precursor can be firmly and evenly grown on the surface of the porous carbon material, and the confinement effect of the active metal particles in the hydrotalcite structure and the high specific surface area of ​​the porous carbon are utilized. In the catalyst obtained after calcination, the dispersion of the active metal component particles can be improved, and at the same time, it has strong structural stability, avoiding metal agglomeration and structural collapse of the catalyst during long-term operation.

[0015] According to some preferred embodiments of the present invention, in step (1), the ratio of the total molar amount of the active metal component precursor and the dispersed component precursor to the molar amount of the Al salt is (1-4):1, for example, it can be a specific but non-limiting molar ratio such as 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, or any range between the two. Preferably, the ratio of the total molar amount of the active metal component precursor and the dispersed component precursor to the molar amount of the Al salt is (2-3):1.

[0016] In the present invention, the selection range of the solvent is relatively wide, as long as it can fully dissolve and disperse the components. From the perspective of cost, preferably, the solvent is water.

[0017] According to the present invention, preferably, in the salt solution, the total molar concentration of the active metal component precursor, the dispersed component precursor, the auxiliary metal precursor and the Al salt is 0.4-1.2 mol / L, preferably 0.6-1.2 mol / L.

[0018] In the present invention, the promoter metal is selected from at least one of rare earth metals, Group VIIB metals, Group IVB metals and Group VIB metals, for example, it may be at least one of Ce, La, Mn, Zr, Mo, W, Cr and Ti, preferably at least one of Ce, Mn, Zr and Mo. The use of the above preferred promoter metals is conducive to the synergistic effect of the promoter metal and the active metal component, and further improves the activity and stability of the prepared hydrogenation catalyst.

[0019] According to the present invention, preferably, the molar ratio of the auxiliary metal precursor to the active metal component precursor is 1: (5-20), for example, it can be 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, 1: 10, 1: 11, 1: 12, 1: 13, 1: 14, 1: 15, 1: 16, 1: 17, 1: 18, 1: 19, 1: 20 and other specific but non-limiting molar ratios or any range between the two, preferably, the molar ratio of the auxiliary metal precursor to the active metal component precursor is 1: (8-15). In the above preferred case, it is beneficial to further improve the hydrogenation efficiency and hydrogenation stability of the prepared hydrogenation catalyst.

[0020] According to some preferred embodiments of the present invention, the specific surface area of ​​the porous carbon is not less than 500 m 2 / g, preferably 500-1000 m 2 / g. In the present invention, the introduction of porous carbon with a high specific surface area into the precipitation reaction in step (2) is beneficial to further improve the service life of the catalyst. The reason may be that the presence of porous carbon with a high specific surface area is beneficial to further improve the dispersibility of the hydrotalcite precursor and improve the structural stability of the catalyst.

[0021] In the present invention, the selection range for the type of porous carbon is relatively wide, and any carbon material that satisfies the above-mentioned pore structure can be applied to the present invention. Preferably, the porous carbon is selected from at least one of activated carbon, carbon black and carbon nanotubes. The length of the carbon nanotubes can be, for example, 10-40 microns, and the aspect ratio can be, for example, 1000-5000. The use of the above-mentioned preferred porous carbon is conducive to further improving the activity and stability of the prepared catalyst.

[0022] The present invention has no particular limitation on the source of the porous carbon, which can be purchased commercially or prepared by any method known in the art. For example, the activated carbon can be coconut shell activated carbon, apricot shell activated carbon, walnut shell activated carbon, etc. The porous carbon can also be porous carbon modified with non-metallic elements such as N and S, and the present invention has no particular limitation on this.

[0023] According to the present invention, by contacting the porous carbon with an acid in step (2), the density of oxygen-containing functional groups on the surface can be increased, providing sufficient sites for the growth of LDH, which is beneficial to further improve the catalytic activity of the prepared catalyst.

[0024] The present invention has no particular limitation on the type of the acid. Preferably, the acid is selected from nitric acid and / or hydrochloric acid, preferably nitric acid.

[0025] Preferably, the acid is provided by an aqueous solution of the acid, and the concentration of the aqueous solution of the acid is 8-13 mol / L.

[0026] Preferably, in step (2), the amount of the acid solution used is 8-50 mL, preferably 10-30 mL, relative to 1 g of the porous carbon.

[0027] Preferably, in step (2), the contact temperature is 60-130°C, preferably 80-110°C, and the contact time is 6-72h, preferably 8-24h.

[0028] The contacting in step (2) is carried out under stirring conditions. In the present invention, the stirring may be magnetic stirring, mechanical stirring or manual stirring, etc. The stirring conditions may be determined by those skilled in the art according to actual conditions.

[0029] According to some preferred embodiments of the present invention, in step (3), the ratio of the amount of the acid-treated porous carbon to the total mass of the metal elements contained in the active metal component precursor, the dispersed component precursor, the auxiliary metal precursor, and the Al salt in the salt solution is 1:(0.2-3), preferably 1:(0.5-1.5).

[0030] According to the present invention, preferably, the surfactant is selected from polyvinyl pyrrolidone (weight average molecular weight of 10000-40000) and / or polyethylene glycol (weight average molecular weight of 2000-7000).

[0031] Preferably, relative to 100 parts by weight of porous carbon, the amount of the surfactant is 10-50 parts by weight, for example, it can be 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, etc., or any range between the two. Preferably, relative to 100 parts by weight of porous carbon, the amount of the surfactant is 15-30 parts by weight. In the above preferred case, it is beneficial to ensure that the hydroxide grows uniformly on the surface of the carbon material without local enrichment, while reducing the amount of surfactant as much as possible.

[0032] According to the present invention, preferably, the alkali is provided by an alkali solution, and the concentration of the alkali in the alkali solution is 0.5-2 mol / L.

[0033] Preferably, the base is selected from sodium hydroxide and / or sodium carbonate, preferably, the base comprises sodium hydroxide and sodium carbonate.

[0034] Preferably, the amount of the base used is such that the pH of the precipitation reaction is 8-10, preferably 8.5-9.5.

[0035] Preferably, the precipitation reaction temperature is 80-110° C., preferably 90-100° C., and the precipitation reaction time is 8-48 h, preferably 12-24 h.

[0036] The present invention has no particular limitation on the order of mixing the substances in step (3). Preferably, step (3) comprises: (3-1) mixing the acid-treated porous carbon, a salt solution, and a surfactant; (3-2) Add a base to the mixture obtained in step (3-1) until the pH is 8-10.

[0037] According to the present invention, step (3) further comprises: solid-liquid separation, washing and drying of the product obtained by the precipitation reaction. The solid-liquid separation, washing and drying can be performed using conventional operation methods and conditions in the art, and the present invention has no particular limitation thereto.

[0038] According to the present invention, preferably, in step (4), the inert atmosphere is provided by nitrogen and / or argon. Preferably, the flow rate of the inert atmosphere is 20-40 mL / min relative to 10 g of the product of the precipitation reaction.

[0039] Preferably, the calcination temperature is 300-700° C., preferably 400-600° C.; the calcination time is 2-10 h, preferably 4-6 h.

[0040] The second aspect of the present invention provides a hydrogenation catalyst prepared by the above preparation method.

[0041] A third aspect of the present invention provides a method for hydrogenating an organic hydrogen storage material, comprising: contacting an organic hydrogen storage material, hydrogen and a catalyst under hydrogenation reaction conditions; Wherein, the catalyst is the hydrogenation catalyst described in the second aspect.

[0042] The hydrogenation method provided by the present invention can be applied to conventional organic liquid hydrogen storage materials in the art, such as aromatic hydrocarbon hydrogen storage materials and / or N-containing heterocyclic hydrogen storage materials. Among them, the aromatic hydrocarbon hydrogen storage material is preferably toluene and / or dibenzylcarbazole, and the N-containing heterocyclic hydrogen storage material is preferably at least one of carbazole, N-ethylcarbazole, N-methylcarbazole, and N-propylcarbazole.

[0043] The present invention has a wide range of selection for the hydrogenation reaction conditions. Preferably, the hydrogenation method provided by the present invention can achieve safe hydrogen storage at a higher liquid space velocity. According to some preferred embodiments of the present invention, the hydrogenation reaction conditions include: a reaction temperature of 130-200°C, preferably 140-180°C; a reaction pressure of 3-8MPa, preferably 4-7MPa; an organic hydrogen storage material space velocity of 0.1-1 mL / g cat / h, preferably 0.3-0.8 mL / g cat / h; hydrogen to oil volume ratio is 2000-8000, preferably 2000-6000. In the above preferred case, it can not only reduce hydrogen storage energy consumption and production costs, but also help improve the safety and stability of the production process.

[0044] In the present invention, preferably, before the contacting, the hydrogenation method further comprises: subjecting the catalyst to a reduction treatment to reduce at least part of the active metal components in the catalyst to a single substance.

[0045] The present invention has no particular limitation on the conditions of the reduction treatment, as long as the above-mentioned reduction purpose can be achieved.

[0046] According to some preferred embodiments of the present invention, the reduction treatment is carried out in the presence of hydrogen, the temperature of the reduction treatment is 350-750°C, preferably 400-550°C; the pressure of the reduction treatment is 0.01-0.2MPa, preferably 0.02-0.1MPa; the time of the reduction treatment is 2-10h, preferably 3-6h; the hydrogen space velocity is 1-30 mL / g cat / min, preferably 2-10mL / g cat / min.

[0047] The present invention will be described in detail below through examples.

[0048] Example 1 (1) Dissolve 7.10 g of nickel nitrate hexahydrate, 12.51 g of magnesium nitrate hexahydrate, 9.49 g of aluminum nitrate nonahydrate, and 1.04 g of cerium nitrate hexahydrate in 100 mL of water to form a uniform salt solution; (2) 6 g of multi-walled carbon nanotubes (length 30 μm, diameter 20 nm, specific surface area 983 m 2 / g) were uniformly dispersed in 120 mL, 10 mol / L concentrated nitric acid, stirred and refluxed at 100°C for 12 hours, and acid-modified carbon nanotubes were obtained after washing; (3) Adding acid-modified carbon nanotubes and 1 g of polyethylene glycol (weight average molecular weight of 7000) to the salt solution of step (1), stirring at room temperature for 30 minutes to obtain a carbon nanotube suspension; dissolving 3.2 g of sodium hydroxide and 8.48 g of sodium carbonate in 100 mL of water to form a mixed alkaline solution; slowly dropping the alkaline solution into the carbon nanotube suspension, controlling the pH at the end point of the dropping to 9, stirring at 95 °C for 24 hours, filtering, washing, and drying to obtain a black precipitate; (4) The black solid powder was ground and calcined at 450 °C for 4 h in a nitrogen atmosphere at 20 mL / min to obtain catalyst cat-1.

[0049] Example 2 (1) Dissolve 10.65 g of nickel nitrate hexahydrate, 6.26 g of magnesium nitrate hexahydrate, 9.49 g of aluminum nitrate nonahydrate, and 0.63 g of manganese nitrate tetrahydrate in 140 mL of water to form a uniform salt solution; (2) 2.5 g coconut shell activated carbon (specific surface area 816 m 2 / g) was evenly dispersed in 40 mL, 8 mol / L concentrated nitric acid, stirred and refluxed at 80°C for 24 hours, and then washed to obtain acid-modified activated carbon; (3) Add acid-modified activated carbon and 0.5 g of polyethylene glycol (weight average molecular weight of 4000) to the salt solution, and stir at room temperature for 30 minutes to obtain an activated carbon suspension; dissolve 3.2 g of sodium hydroxide and 8.48 g of sodium carbonate in 200 mL of water to form a mixed alkaline solution; slowly drop the alkaline solution into the activated carbon suspension, control the pH value at the end point of the dropwise addition to 9.5, stir at 90 °C for 12 hours, filter, wash, and dry to obtain a black precipitate; (4) The black solid powder was ground and calcined at 500 °C for 6 h in a nitrogen atmosphere at 30 mL / min to obtain catalyst cat-2.

[0050] Example 3 (1) Dissolve 13.10 g of cobalt nitrate hexahydrate, 13.39 g of zinc nitrate hexahydrate, 16.88 g of aluminum nitrate nonahydrate, and 1.97 g of zirconium nitrate trihydrate in 120 mL of water to form a uniform salt solution; (2) 7 g of N-doped carbon black (with a specific surface area of ​​503 m 2 / g, N content of 8.3 wt%) was uniformly dispersed in 140 mL, 12 mol / L concentrated nitric acid, stirred and refluxed at 110°C for 8 hours, and then washed to obtain acid-modified N-doped carbon black; (3) Add acid-modified N-doped carbon black and 2.0 g of polyvinyl pyrrolidone (weight average molecular weight of 10,000) to the salt solution, and stir at room temperature for 30 minutes to obtain an N-doped carbon black suspension; dissolve 4.5 g of sodium hydroxide and 12.0 g of sodium carbonate in 120 mL of water to form a mixed alkaline solution; slowly drop the alkaline solution into the N-doped carbon black suspension, control the pH at the end point of the dropwise addition to 8.5, stir at 100 °C for 18 hours, filter, wash, and dry to obtain a black precipitate; (4) The black solid powder was ground and calcined at 600 °C for 5 h in a nitrogen atmosphere at 40 mL / min to obtain catalyst cat-3.

[0051] Example 4 (1) Dissolve 11.64 g of nickel nitrate hexahydrate, 5.82 g of cobalt nitrate hexahydrate, 10.11 g of zinc nitrate hexahydrate, 12.75 g of aluminum nitrate nonahydrate, and 3.26 g of cerium nitrate hexahydrate in 130 mL of water to form a uniform salt solution; (2) 6 g of apricot shell activated carbon (specific surface area: 961 m 2 / g) was evenly dispersed in 150 mL, 13 mol / L concentrated nitric acid, stirred and refluxed at 80°C for 18 hours, and then washed to obtain acid-modified activated carbon; (3) Add acid-modified activated carbon and 1.5 g of polyethylene glycol (weight average molecular weight of 6000) to the salt solution, and stir at room temperature for 30 minutes to obtain an activated carbon suspension; dissolve 3.2 g of sodium hydroxide and 8.48 g of sodium carbonate in 250 mL of water to form a mixed alkaline solution; slowly add the alkaline solution dropwise to the activated carbon suspension, control the pH at the end point of the addition to be 9, stir at 100 °C for 24 hours, filter, wash, and dry to obtain a black precipitate; (4) The black solid powder was ground and calcined at 400 °C for 4 h in a nitrogen atmosphere at 20 mL / min to obtain catalyst cat-4.

[0052] Example 5 (1) Dissolve 19.67 g of nickel nitrate hexahydrate, 8.72 g of magnesium nitrate hexahydrate, 12.75 g of aluminum nitrate nonahydrate, and 1.49 g of ammonium heptamolybdate tetrahydrate in 150 mL of water to form a uniform salt solution; (2) 6 g of walnut shell activated carbon (specific surface area 693 m 2 / g) was evenly dispersed in 60 mL, 12 mol / L concentrated nitric acid, stirred and refluxed at 100 °C for 12 hours, and then washed to obtain acid-modified activated carbon; (3) Add acid-modified activated carbon and 1 g of polyethylene glycol (weight average molecular weight of 7000) to the salt solution, and stir at room temperature for 30 minutes to obtain an activated carbon suspension; dissolve 4.5 g of sodium hydroxide and 12.0 g of sodium carbonate in 200 mL of water to form a mixed alkaline solution; slowly drop the alkaline solution into the activated carbon suspension, control the pH at the end point of the dropwise addition to 9, stir at 95 °C for 18 hours, filter, wash, and dry to obtain a black precipitate; (4) The black solid powder was ground and calcined at 550 °C for 4 h in a nitrogen atmosphere at 20 mL / min to obtain catalyst cat-5.

[0053] Example 6 (1) Dissolve 9.84 g of cobalt nitrate hexahydrate, 6.67 g of magnesium nitrate hexahydrate, 9.38 g of aluminum nitrate nonahydrate, and 0.74 g of ammonium heptamolybdate tetrahydrate in 140 mL of water to form a uniform salt solution; (2) 4 g coconut shell activated carbon (specific surface area 850 m 2 / g) was uniformly dispersed in 120 mL, 10 mol / L concentrated nitric acid, stirred and refluxed at 100°C for 20 hours, and then washed to obtain acid-modified activated carbon; (3) Add acid-modified activated carbon and 1 g of polyvinyl pyrrolidone (weight-average molecular weight of 40,000) to the salt solution, and stir at room temperature for 30 minutes to obtain an activated carbon suspension; dissolve 4.5 g of sodium hydroxide and 12.0 g of sodium carbonate in 200 mL of water to form a mixed alkaline solution; slowly drop the alkaline solution into the activated carbon suspension, control the pH at the end point of the dropwise addition to 9, stir at 95 °C for 12 hours, filter, wash, and dry to obtain a black precipitate; (4) The black solid powder was ground and calcined at 450°C for 4 hours in a nitrogen atmosphere at a flow rate of 30 mL / min to obtain catalyst cat-6.

[0054] Example 7 The method of Example 1 was followed, except that the amount of multi-walled carbon nanotubes added was 2 g.

[0055] The obtained catalyst was designated as cat-7.

[0056] Example 8 The method of Example 1 was followed except that an equal mass of coal-based activated carbon (with a specific surface area of ​​354 m 2 / g) to replace multi-walled carbon nanotubes. The obtained catalyst is recorded as cat-8.

[0057] Example 9 The method of Example 2 was followed, except that the pH at the end point of the alkali addition was controlled to be 8.0. The obtained catalyst was recorded as cat-9.

[0058] Example 10 The method of Example 2 was followed, except that the base was added dropwise and the mixture was stirred at 50°C for 12 hours. The obtained catalyst was designated as cat-10.

[0059] Comparative Example 1 (1) Dissolve 7.10 g of nickel nitrate hexahydrate, 12.51 g of magnesium nitrate hexahydrate, 9.49 g of aluminum nitrate nonahydrate, and 1.04 g of cerium nitrate hexahydrate in 100 mL of water to form a uniform salt solution; (2) Dissolve 3.2 g of sodium hydroxide and 8.48 g of sodium carbonate in 100 mL of water to form a mixed alkaline solution; slowly add the alkaline solution dropwise to the salt solution, control the pH value at the end point of the addition to be 9, stir at 95 °C for 24 hours, filter, wash, and dry to obtain LDH; (3) 6 g of multi-walled carbon nanotubes (length 30 μm, diameter 20 nm, specific surface area 983 m 2 / g) were uniformly dispersed in 120 mL, 10 mol / L concentrated nitric acid, stirred and refluxed at 100°C for 12 hours, and acid-modified carbon nanotubes were obtained after washing; (4) LDH and acid-modified carbon nanotubes were ground in an agate mortar for 30 min and calcined at 450 °C for 4 h in a nitrogen atmosphere at 30 mL / min to obtain a mechanically mixed catalyst, which was designated as Dcat-1.

[0060] Comparative Example 2 The method of Example 2 was followed, except that polyethylene glycol was not added. The obtained catalyst was recorded as Dcat-2.

[0061] Comparative Example 3 The method of Example 2 was followed, except that manganese nitrate tetrahydrate was not added to the raw material. The obtained catalyst was recorded as Dcat-3.

[0062] The following test examples are used to illustrate the hydrogenation method of the organic hydrogen storage material of the present invention. Test Example 1 The catalyst cat-1 prepared in Example 1 was ground, shaped and granulated to obtain particles of 20-40 mesh. 5 g of the catalyst particles were loaded into an isothermal fixed bed reactor and reduced for 4 h at a hydrogen flow rate of 25 mL / min, 400 °C and 0.1 MPa. The temperature was then lowered to 160 °C, the hydrogen pressure was increased to 4 MPa, and N-ethylcarbazole (NEC) was delivered into the reactor at a flow rate of 0.05 mL / min through a high-pressure metering pump. 2 / reaction raw material volume ratio is 4000. After 12 h of reaction, samples were taken to analyze the product component content and the hydrogenation rate, mass hydrogen storage rate and unit hydrogen storage capacity were calculated.

[0063] Hydrogenation rate (%) = ; Mass hydrogen storage rate (wt%) = ; Unit hydrogen storage capacity (g 氢气 / h / kg 催化剂 )= .

[0064] Test Example 2-8 The method of Test Example 1 is followed, except that cat-2 to cat-8 are used to replace cat-1, and the hydrogen storage medium and reaction conditions used are shown in Table 1.

[0065] Comparative test examples 1-3 The method of test example 1 is followed, except that Dcat-1 to Dcat-3 are used to replace cat-1. The results are shown in Table 1.

[0066] Table 1

[0067] It can be seen from the results in Table 1 that the LDH-carbon material composite catalyst prepared in the embodiment of the present invention has a high activity for the hydrogenation of liquid hydrogen storage materials, so that the mass hydrogen storage rates of NEC, toluene and dibenzyltoluene can reach 5.75wt%, 5.54wt% and 5.63wt%, respectively.

[0068] Taking the sample obtained by simple mechanical mixing of LDH and carbon material as a comparison, the hydrogenation rate and unit hydrogen storage capacity of the sample in Example 1 are significantly lower than those of the composite catalyst described in Examples 1-6. The sample in Example 2 has a significantly reduced hydrogenation activity for NEC. This is because the lack of surfactant in the synthesis process causes the growth of LDH on the activated carbon to be extremely uneven and the dispersion is reduced. In addition, the hydrogenation activity of the sample in Example 1 decreases significantly with the extension of the operating time. It can be seen that the catalyst prepared by the preparation method provided by the present invention uses non-precious metals as active components, the preparation method is simple, the conditions are mild, it is suitable for large-scale production and industrial applications, and it is more motivated to promote the commercialization and market promotion of technology.

[0069] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a hydrogenation catalyst, characterized in that: The preparation method comprises: (1) mixing an active metal component precursor, a dispersed component precursor, an auxiliary metal precursor, an Al salt and a solvent to obtain a salt solution; Wherein, the active metal component is selected from Ni and / or Co, the dispersed component is selected from Zn and / or Mg, and the auxiliary metal is selected from at least one of rare earth metals, Group VIIB metals, Group IVB metals and Group VIB metals; (2) contacting the porous carbon with an acid under stirring conditions to obtain acid-treated porous carbon; (3) mixing the acid-treated porous carbon, salt solution, surfactant and alkali to carry out a precipitation reaction; (4) calcining the product obtained in step (3) under an inert atmosphere.

2. The preparation method according to claim 1, wherein In step (1), the ratio of the total molar amount of the active metal component precursor and the dispersed component precursor to the molar amount of the Al salt is (1-4):1, preferably (2-3):1; Preferably, the solvent is water; Preferably, in the salt solution, the total molar concentration of the active metal component precursor, the dispersed component precursor, the auxiliary metal precursor and the Al salt is 0.4-1.2 mol / L, preferably 0.6-1.2 mol / L.

3. The preparation method according to claim 1 or 2, wherein The auxiliary metal is selected from at least one of Ce, Mn, Zr and Mo; Preferably, the molar ratio of the auxiliary metal precursor to the active metal component precursor is 1:(5-20), preferably 1:(8-15).

4. The preparation method according to any one of claims 1 to 3, wherein The specific surface area of ​​the porous carbon is not less than 500 m 2 / g, preferably 500-1000m 2 / g; Preferably, the porous carbon is selected from at least one of activated carbon, carbon black and carbon nanotubes.

5. The preparation method according to any one of claims 1 to 4, wherein: The acid in step (2) is selected from nitric acid and / or hydrochloric acid; Preferably, the acid is provided by an aqueous solution of the acid, and the concentration of the aqueous solution of the acid is 8-13 mol / L; Preferably, in step (2), the amount of the acid solution is 8-50 mL relative to 1 g of the porous carbon; Preferably, in step (2), the contact temperature is 60-130°C, preferably 80-110°C, and the contact time is 6-72h, preferably 8-24h.

6. The preparation method according to any one of claims 1 to 5, wherein: In step (3), the ratio of the amount of the acid-treated porous carbon to the total mass of the metal elements contained in the active metal component precursor, the dispersed component precursor, the auxiliary metal precursor, and the Al salt in the salt solution is 1:(0.2-3), preferably 1:(0.5-1.5); Preferably, the surfactant is selected from polyvinyl pyrrolidone and / or polyethylene glycol; Preferably, the amount of the surfactant is 10-50 parts by weight relative to 100 parts by weight of the porous carbon.

7. The preparation method according to any one of claims 1 to 6, wherein: The alkali is provided by an alkali solution, wherein the concentration of the alkali in the alkali solution is 0.5-2 mol / L; Preferably, the base is selected from sodium hydroxide and / or sodium carbonate, preferably sodium hydroxide and sodium carbonate; Preferably, the amount of the base is such that the pH of the precipitation reaction is 8-10; Preferably, the precipitation reaction temperature is 80-110°C and the time is 8-48h; Preferably, in step (4), the inert atmosphere is provided by nitrogen and / or argon; Preferably, the calcination temperature is 300-700° C., and the calcination time is 2-10 h.

8. A hydrogenation catalyst obtained by the preparation method according to any one of claims 1 to 7.

9. A method for hydrogenating an organic hydrogen storage material, comprising: Under hydrogenation reaction conditions, an organic hydrogen storage material, hydrogen gas and a catalyst are contacted; Wherein, the catalyst is the hydrogenation catalyst according to claim 8; Preferably, the organic hydrogen storage material is selected from aromatic hydrocarbon hydrogen storage materials and / or N-containing heterocyclic hydrogen storage materials, the aromatic hydrocarbon hydrogen storage material is preferably toluene and / or dibenzylcarbazole, and the N-containing heterocyclic hydrogen storage material is preferably at least one of carbazole, N-ethylcarbazole, N-methylcarbazole, and N-propylcarbazole; Preferably, the hydrogenation reaction conditions include: reaction temperature of 140-180°C, reaction pressure of 3-8 MPa, organic hydrogen storage material space velocity of 0.1-1 mL / g cat / h, the volume ratio of hydrogen to oil is 2000-8000.

10. The hydrogenation method according to claim 9, wherein: Prior to the contacting, the hydrogenation method further comprises: subjecting the catalyst to a reduction treatment; Preferably, the reduction treatment is carried out in the presence of hydrogen, the temperature of the reduction treatment is 350-750 °C, the pressure of the reduction treatment is 0.01-0.2 MPa, the time of the reduction treatment is 2-10 h, and the hydrogen space velocity is 1-30 mL / g cat / min.

Citation Information

Patent Citations

  • High-activity and high-stability supported nickel catalyst as well as preparation method and application thereof

    CN112675865A

Cited By

  • Hydrophobic catalyst for water-phase hydrogenation of alpha, beta-unsaturated aldehyde and preparation method of hydrophobic catalyst

    CN122462064A

  • A hydrophobic catalyst for the hydrogention of alpha, beta-unsaturated aldehydes in aqueous phase and a process for its preparation

    CN122462064B